Study Of Social And Pedagogical Factors In International Evaluation Research - Akramjon Mukhtorovich Matkarimov (Zien Journals, 2025)
In the countries participating in the international evaluation studies, the issue of researching the success of students in education is given wide attention. The success of students in education depends on such factors as the educational process, educational programs, methods, educational literature in secondary schools. Also, the proof that socio-pedagogical factors, such as the students' family conditions, the educational environment in their families, and their parents' attitude towards education are of decisive importance, is reflected in scientific research
Keywords: international assessment research; pedagogical research; family